2003
DOI: 10.1143/jjap.42.l1472
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of O(3P) Density in O2and Kr Gas Mixture Remote Plasma Oxidation of Silicon Measured by Two-Photon Absorption Laser-Induced Fluorescence

Abstract: We show how the general approaches based on the order parameter concept and the slaving principle, so far developed for classical systems, can be extended to quantum systems. Possible applications are the formation of spatial or temporal structures formed by electrons or holes in semiconductors ( G u m effect and filamentation).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 3 publications
2
4
0
Order By: Relevance
“…Kamioka et al investigated the relation between surface O( 3 P) density and SiO 2 growth rate. 23) Their results indicated that the exposure to O( 3 P) of 10 15 (10 14 ) cm À3 density, a SiO 2 growth rate of 9 nm/30 min (3 nm/30 min) can be achieved at 500 C, which is comparable to our oxidation rate for the side-flow (down-flow) chamber. Therefore, only 1% (or 0.1% for down-flow chamber) of the ozone molecules arrive at the surface and serve as an oxygen supplier.…”
Section: Optimization Of Sio 2 Film Formationsupporting
confidence: 61%
See 1 more Smart Citation
“…Kamioka et al investigated the relation between surface O( 3 P) density and SiO 2 growth rate. 23) Their results indicated that the exposure to O( 3 P) of 10 15 (10 14 ) cm À3 density, a SiO 2 growth rate of 9 nm/30 min (3 nm/30 min) can be achieved at 500 C, which is comparable to our oxidation rate for the side-flow (down-flow) chamber. Therefore, only 1% (or 0.1% for down-flow chamber) of the ozone molecules arrive at the surface and serve as an oxygen supplier.…”
Section: Optimization Of Sio 2 Film Formationsupporting
confidence: 61%
“…21,22) Also in the case of remote plasma oxidation, growth rate increased with O( 3 P) density in the gas phase as estimated by laser-induced fluorescence measurement. 23) From these results, we assume that in the case of the sideflow 12 mm 2 chamber, the number of oxidants (i.e., O( 3 P)) adjacent to the surface in the gas phase increases with processing pressure, while in the down-flow 4 inch chamber, it remains at a much lower level independent of processing pressure. The results that the rate of oxidation by HC-O 3 is not so enhanced compared with that by 10 vol.% O 3 under the same processing conditions (see Fig.…”
Section: Optimization Of Sio 2 Film Formationmentioning
confidence: 98%
“…The O-atom densities obtained in plasma processes are generally higher than that obtained in the present study. Especially, high-density O atoms have been observed in microwave discharges and the decomposition efficiency of O 2 can be as high as 30%, which corresponds to the O-atom density of the order of 10 15 cm -3 [20,24]. The O-atom density in catalytic decomposition may be increased by one order by using a larger chamber and a longer filament.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the ground-state oxygen atom [O( 3 P)] and the first-excited-state oxygen atom [O( 1 D)] are the main species for achieving low-temperature oxidation, 13) oxidation would be enhanced by generating O( 3 P) and O( 1 D) atoms from ozone at wavelengths even longer than those used in conventional photo oxidation.…”
Section: Introductionmentioning
confidence: 99%